Polyurethane rigid foam with dimensional stability and preparation method thereof

By using water -containing alcohol compositions and specific polymer polyol compositions, the problem of excessive response and high brittleness during the spraying process of polyurethane foam is solved, and a polyurethane hard foam with stable size, low crispy and high toughness.

CN119350574APending Publication Date: 2025-01-24SHANDONG UNIV OF TECH +1
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202310911282.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-24
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In the prior art, in the spraying process of polyurethane foam, the use of highly reactive polyether polyols and high CO2 foaming agents leads to excessive reaction, the wet foam is prone to fall off, and the foam after curing is highly brittle, easily shrinking and deforming. , causing cracks to form, especially in cold winters.

Method used

Using water -containing alcohol composition (AC), including ethanol benanol and ethanol dilitanol, it has lower alkaline and reaction activity, low CO2 content and high liquidity, combined with specific polymer diversified diversification Alcohol composition is used to prepare stable and low -crispy polyurethane hard foam.

Benefits of technology

Effectively avoid the problem of wet foam drop and high foam crispyness, improve the size stability and toughness of the foam, extend the time of gel, shorten the solidification time, and improve the borders and overall performance of the foam.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350574A_ABST
    Figure CN119350574A_ABST
Patent Text Reader

Abstract

The invention relates to polyurethane rigid foam with dimensional stability and a preparation method thereof. The preparation method comprises the following steps: mixing polyisocyanate and a polymer polyol composition, and spraying and foaming, the polymer polyol composition comprises (I) 100 parts by weight of polymer polyol, and the polymer polyol composition comprises: 1) 50-60 wt% of pentaerythritol starting polyether polyol; (2) 14 to 22 weight percent of polycarbonate polyol; 3) from 9 to 15 wt% of a sorbitol starting polyether polyol; 4) 6 to 12 wt% of polytetrahydrofuran ether glycol; 5) 4 to 8 wt% of glycerol starting polyether polyol; (II) 1.5-6.5 parts by weight of a catalyst and a foam stabilizer; (III) 0-18 parts by weight of a flame retardant; (III) 8-16 parts by weight of ethanol sec-butyl alcohol amine and ethanol di-sec-butyl alcohol amine carbonate (AC) as a foaming agent. The foams have good compressive strength and dimensional stability, low brittleness and good thermal insulation properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a spray-type dimensionally stable, low-brittle polyurethane rigid foam and a preparation method thereof. The present invention also relates to a foaming polymer polyol composition (white material) comprising a novel organic alcohol amine carbonate foaming agent and a polymer polyol. The composition is used for reacting with isocyanate to prepare a dimensionally stable, low-brittle polyurethane rigid foam. Background Art

[0002] Polyurethane rigid foam material is a high-quality thermal insulation material, widely used in refrigerators, freezers, water heaters, cold chain insulation and other industries.

[0003] The market prospect of polyurethane spraying is broad, and the demand for foaming agents is huge. At present, in the field of building exterior wall spraying and pipe winding spraying, people have higher and higher requirements for energy saving and carbon reduction. Therefore, the selection of environmentally friendly foaming agents for the preparation of polyurethane insulation materials in this field is becoming more and more stringent.

[0004] Generally, the polyurethane rigid foam material formed by spraying is prepared by mixing and spraying a polymer polyol composition (white material) with a polyisocyanate (black material), and reacting and curing, wherein the white material contains a polymer polyol of polyether polyol and aromatic polyester polyol (e.g. polyethylene phthalate polyol) and / or toluene diamine polyether polyol as main raw materials, and contains auxiliary agents such as blowing agents, catalysts and foam stabilizers.

[0005] US6326412 B1 discloses ammonium carbamate as a polyurethane foaming agent, wherein the viscosity of the ammonium carbamate is as high as 2200 mPa.s (see lines 51-55 in column 6 of the specification), and the ammonium carbamate is in a viscous or semi-solid state.

[0006] At present, in the case of using a composite foaming agent containing more water, for example, in a foaming agent composed of water and cyclopentane or in a foaming agent composed of water and a hydrofluorocarbon physical foaming agent, if the amount of water used is large, the polyurethane foam formed has a higher open porosity, its size is unstable (prone to shrinkage and deformation), and its thermal insulation performance will decrease.

[0007] In addition, in the spraying process of polyurethane foam, the white material (polymer polyol component A) and the black material (isocyanate component B) are usually mixed by a sprayer (and then sprayed on the surface of a substrate (such as a steel plate, a steel pipe, or a concrete structure such as a wall) through a spray gun. Generally, the spraying and foaming are carried out in a spraying manner of 2-3 cm per layer and a total thickness of 20-30 cm. The foam is then formed and cured to obtain a polyurethane rigid foam as a thermal insulation material layer.

[0008] In the prior art, if a polyether polyol composition with high reactivity is used in a large amount and a foaming agent composition (or amine composition) with a high CO2 content is used, the reaction is too rapid in the early stage of the foaming reaction (the reaction system has not yet fully gelled) during the spraying operation, and the foaming agent composition (or amine composition) with a high CO2 content is heated and quickly releases a large amount of CO2 gas, causing the wet foam sprayed onto the (stainless steel or concrete) substrate or onto the cured foam layer to expand rapidly and fall off the substrate. In addition, if the cured foam has high brittleness, it will shrink and deform slightly, resulting in cracks between the cured foam material and the substrate or between two adjacent cured foam layers. These problems are particularly prominent when spraying in cold winter.

[0009] In addition, in the prior art, aqueous alcohol amines (e.g., carbonates of primary amine alcohol amines (e.g., ethanolamines), and carbonates of some secondary amine diol amines, e.g., carbonate di(diethanolamine) salts, etc.) are used as foaming agents. These alcohol amines have a greater influence on the urethanization reaction between the polymer polyol composition (white material) containing an amine catalyst and polyisocyanates (black material). In particular, some amine foaming agents affect the catalytic action of the amine catalyst, e.g., causing an excessively fast reaction speed in the early stage and insufficient curing reaction in the later stage, affecting the strength of the foam material, and causing the foam material to be dimensionally unstable (high opening rate, easy to shrink and deform). In addition, when aqueous alcohol amines (e.g., triethanolamine hydrate) are used as foaming agents for preparing a spray-coated polyurethane rigid foam with a relatively large thickness, during the spraying process, because the reaction speed is relatively fast and heat is quickly released, a "core burning" phenomenon occurs inside the foam material, which reduces the thermal insulation performance of the foam material, and even causes the foam material to crack from the substrate to form cracks or to crack between two adjacent foam layers to form cracks.

[0010] In addition, US2622099A, US4169856A, US2051486A, GB448373A, GB710861A, GB1387573A, GB642950A, GB760215A, GB655580A and CA1003358A disclose isopropanolamine, ethanolamine or butanolamine prepared by the reaction of aqueous ammonia with propylene oxide or ethylene oxide.

[0011] CN107663157A and CN103435499A disclose methods for producing ethanol diisopropanolamine by reacting ethanolamine with propylene oxide, but do not disclose that the product can be used as a PU foaming agent.

[0012] So far, the organic alcohol amine carbonates in the prior art have not been successfully used as blowing agents in the spray foaming of polyurethane foams. In addition, the combination of polyethers can obtain high-hardness, high-strength polyurethane rigid foams, but how to improve the toughness of the foam and reduce its brittleness is a difficult problem. Summary of the invention

[0013] In order to solve the technical problems existing in the prior art, the inventors of the present application firstly provide an aqueous alkanolamine composition (AC) (or referred to as an aqueous alkanolamine mixture or an alkanolamine hydrate) containing ethanol sec-butanolamine and ethanol di-sec-butanolamine for polyurethane foam spraying, characterized in that it has lower alkalinity and activity in reaction with isocyanate, lower CO2 content and higher fluidity. Compared with the salts of alkanolamines with two or three carbon atoms (diethanolamine carbonate and diisopropanolamine carbonate), ethanol sec-butanolamine and ethanol di-sec-butanolamine have lower reactivity and PU catalytic effect. The inventors found that ethanol sec-butanolamine and ethanol di-sec-butanolamine have good compatibility with pentaerythritol starting polyether polyol.

[0014] Wherein a part of ethanol sec-butanolamine and ethanol di-sec-butanolamine forms carbonate with CO2 and water, that is, wherein the ethanolamine is partially salified. This ethanolamine composition (AC) is used as a foaming agent alone, and uses polycarbonate polyol and polytetrahydrofuran ether glycol as toughening components, and is used in polyurethane foam spraying to prepare dimensionally stable, low-brittle polyurethane rigid foam. In addition, the foaming agent of the present invention can delay the gel time of polyurethane foam, and shorten the curing time. For example, when using common ethanolamine (such as diisopropylamine carbonate or diethanolamine carbonate) as a foaming agent, the gel time of the foam sprayed is generally 50-60 seconds, but, when using the present invention containing CO2 and water-containing ethanolamine composition (AC), the gel time of the foam sprayed is generally 70-90 seconds.

[0015] Secondly, the inventors of the present application provide a foaming polymer polyol composition for preparing polyurethane rigid foam, i.e., a polyurethane foaming white material. By selecting several special polymer polyols in combination with the CO2-containing and water-containing alcohol amine composition (AC) of the present invention as a foaming agent, the initial adhesion strength (the sprayed wet foam will not fall off the substrate at a normal spraying speed) and the curing strength (no peeling occurs between the foam and the substrate after the foam is cured) between the sprayed PU foam layer and the substrate (e.g., steel, such as a steel plate or a steel pipe) or a concrete substrate are improved. In particular, the above-mentioned foam delamination problem encountered when the foam is sprayed onto the surface of a metal and concrete substrate at low temperatures in winter is overcome.

[0016] The invention provides a polymer polyol composition (white material) for foaming comprising a novel organic alcohol amine carbonate foaming agent and a polymer polyol alcohol. The composition is used for reacting with isocyanate to prepare dimensionally stable, low-brittle polyurethane rigid foam, especially for preparing spray-type dimensionally stable, low-brittle polyurethane rigid foam.

[0017] According to a first aspect of the present invention, the present invention provides a dimensionally stable, low-brittle polyurethane rigid foam, which is formed by mixing a polyisocyanate with a polymer polyol composition (i.e., white material) and spraying and foaming, wherein the polymer polyol composition comprises or consists of the following components:

[0018] (I) 100 parts by weight of a polymer polyol comprising: 1) 50-60 wt% (preferably 52-58 wt%, such as 54, 55, 56 wt%) of a pentaerythritol-initiated polyether polyol (preferably a pentaerythritol-initiated polyoxypropylene polyol) having a hydroxyl value in the range of 430-580 mgKOH / g (preferably 440-570 mgKOH / g, more preferably 450-560 mgKOH / g, such as 460, 470, 480, 490, 500, 510, 520, 530, 540, 550); 2) 14-22wt% (preferably 16-20wt%, for example 18wt%) of polycarbonate polyol (for example bisphenol A polycarbonate polyol and / or bisphenol F polycarbonate polyol), whose hydroxyl value is in the range of 100-280mgKOH / g (preferably 110-270mgKOH / g, such as 120, 130, 140, 150, 180, 200, 220, 240, 250, 260); 3) 9-15wt% (preferably 10-14wt%, for example 11, 12, 13%) of sorbitol-based polyether polyol (preferably sorbitol-based polyoxypropylene polyol), having a hydroxyl value in the range of 340-520 mgKOH / g (preferably 350-500 mgKOH / g, such as 360, 370, 380, 400, 470, 490); 4) 6-12 wt% (preferably 7-11 wt%, such as 8, 9, 10 wt%) of polytetrahydrofuran ether glycol, having a number average molecular weight in the range of 800-2500, preferably 1000-2000; 5) 4-8 wt% (preferably 10-25 wt%) of polytetrahydrofuran ether glycol, having a number average molecular weight in the range of 800-2500, preferably 1000-2000; 6) 4-8 wt% (preferably 10-25 wt%) of polytetrahydrofuran ether glycol, having a number average molecular weight in the range of 800-2500, preferably 1000-2000; 5-7wt%, for example 6wt%) of glycerol-started polyether polyol (preferably glycerol-started polyoxypropylene polyol) having a hydroxyl value in the range of 220-440mgKOH / g (preferably 230-430mgKOH / g, such as 240, 250, 260, 270, 280, 300, 320, 340, 350, 370, 380, 400 or 420); wherein the weight percentage is based on the total amount of components 1)-5) (i.e., the sum of the percentages of components 1)-component 5) is 100wt%);

[0019] (II) 1.5-6.5 parts by weight (preferably 1.8-6.0 parts by weight, such as 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5 parts by weight) of a catalyst and a foam stabilizer as auxiliary agents; for example, the auxiliary agent includes 0.5-2.5 parts by weight (such as 1 or 1.5 or 2 parts by weight) of a catalyst, 1-4 parts by weight (such as 1.5, 2, 2.5, 3 or 3.5 parts by weight) of a foam stabilizer, relative to 100 parts by weight of the polymer polyol;

[0020] (III) 0-18 parts by weight of a flame retardant (as an auxiliary agent), more preferably 0-16 parts by weight, such as 4, 5, 6, 8, 10, 15, 17 parts by weight of a flame retardant, relative to 100 parts by weight of the polymer polyol;

[0021] (IV) 8-16 parts by weight (preferably 8.5-15.5 parts by weight, 9-15 parts by weight, 9.5-14.5 parts by weight, more preferably 10-14 parts by weight, preferably 10.5-13.5 parts by weight, preferably 11-13 parts by weight, such as 11.5, 12, 12.5 parts by weight) of a CO2- and water-containing olamine composition (AC) as a blowing agent, relative to 100 parts by weight of the polymer polyol; the olamine composition (AC) comprises or consists of or is mainly composed of the following components:

[0022] (1) ethanol sec-butanolamine (A1);

[0023] (2) ethanol di-sec-butanolamine (A2); and

[0024] (3) Water;

[0025] Wherein, the molar ratio of ethanol di-sec-butanolamine (A2) to ethanol sec-butanolamine (A1) is (0.2-6):1, preferably (0.25-5.5):1, preferably (0.3-5):1, preferably (0.4-4.5):1, preferably (0.5-4):1, (0.6-3.8):1, preferably (0.7-3.5):1, preferably (0.8-3.3):1, preferably (0.9-3.2):1, preferably (1-3):1, preferably (1.2-2.8):1;

[0026] wherein the water content is 9-30wt%, preferably 10-29wt%, preferably 11-28wt%, preferably 12-27wt%, preferably 13-26wt%, preferably 14-25wt%, preferably 15-24wt%, preferably 16-23wt%, preferably 17-22wt%, based on the total weight of the (final) alcoholamine composition (AC);

[0027] wherein the total content of (A1) + (A2) + water is 92-100 wt %, preferably 93-100 %, preferably 94-100 %, preferably 95-100 %, preferably 96-100 %, preferably 97-100 %, preferably 98-100 %, preferably 99-100 %, such as 99.5 or 99.8 % or 99.9 %, based on the total weight of the (final) alkanolamine composition (AC);

[0028] Wherein, a portion of the alkanolamines in the alkanolamine composition (AC) is neutralized by CO2 so that the CO2 content in the alkanolamine composition (AC) is 1-6wt%, preferably 1.2-5.5wt%, preferably 1.5-5.0wt%, preferably 1.8-4.7wt%, preferably 2-4.5wt%, preferably 2.5-4.0wt%, such as 3 or 3.5wt%, based on the total weight of the (final) alkanolamine composition (AC).

[0029] According to the first aspect of the present invention, the present invention also provides a method for preparing the above-mentioned dimensionally stable, low-brittle polyurethane rigid foam, which comprises: mixing polyisocyanate with the polymer polyol composition and spraying and foaming.

[0030] Preferably, at an ambient temperature of 25°C, the CO2- and water-containing alkanolamine composition (AC) is in the form of a homogeneous liquid having a pressure of 200-1000 centipoise (25°C), preferably 250-900 centipoise (e.g. 300, 400, 500, 600, 700, 800 centipoise).

[0031] Preferably, the alcoholamine composition (AC) is prepared by the following preparation method:

[0032] 1) allowing ethanolamine to react with 1,2-butylene oxide in the presence of water to obtain an ethanolamine composition (AC) containing ethanol di-sec-butylamine (A2) and ethanol sec-butylamine (A1); wherein the molar ratio of 1,2-butylene oxide to ethanolamine is (1.2-1.9):1, preferably (1.3-1.85):1, preferably (1.4-1.83):1, preferably (1.5-1.8):1; and the ethanolamine composition can be used in the next step without purification;

[0033] Wherein, the amount of water used in step 1) should be such that the water content in the obtained alkanolamine composition (AC) is as defined above; for example, such that the water content in the (final) alkanolamine composition (AC) is 9-30wt%, preferably 10-29wt%, preferably 11-28wt%, preferably 12-27wt%, preferably 13-26wt%, preferably 14-25wt%, preferably 15-24wt%, preferably 16-23wt%, preferably 17-22wt%, based on the total weight of the (final) alkanolamine composition (AC).

[0034] 2) introducing CO2 gas into the obtained alcoholamine composition (AC) to partially neutralize the alcoholamine compound in the composition (AC), thereby obtaining a (final) alcoholamine composition (AC) containing CO2 and water;

[0035] Among them, the amount of CO2 introduced should be such that the CO2 content in the (final) alkanolamine composition (AC) is 1-6wt%, preferably 1.2-5.5wt%, preferably 1.5-5.0wt%, preferably 1.8-4.7wt%, preferably 2-4.5wt%, preferably 2.5-4.0wt%, such as 3 or 3.5wt%, based on the total weight of the (final) alkanolamine composition (AC).

[0036] Preferably, in the (final) obtained alkanolamine composition (AC), the total content of (A1) + (A2) + water is as defined above, i.e. 92-100 wt %, preferably 93-100 %, preferably 94-100 %, preferably 95-100 %, preferably 96-100 %, preferably 97-100 %, preferably 98-100 %, preferably 99-100 %, such as 99.5 %, 99.8 %, 99.9 %, based on the total weight of the (final) alkanolamine composition (AC).

[0037] Alternatively, the alcoholamine composition (AC) is prepared by the following preparation method:

[0038] 1) Preparation of ethanol sec-butanolamine: react ethanolamine with 1,2-butylene oxide in the presence of water at a molar ratio of about (0.95-1.05):1 (e.g., about 1:1) to obtain ethanol sec-butanolamine (A1); it can be used in the subsequent step 3) without purification;

[0039] 2) Preparation of ethanol di-sec-butanolamine: react ethanolamine with 1,2-butylene oxide in the presence of water at a molar ratio of about 1:(1.9-2.1) (e.g., about 1:2) to obtain ethanol di-sec-butanolamine (A2); it can be used in the subsequent step 3) without purification;

[0040] 3) Preparation of an alcoholamine composition (AC): mixing the product of step 1) and the product of step 2), and optionally adding (a small amount of) water to obtain an alcoholamine composition (AC); wherein the amounts of ethanol di-sec-butanolamine (A2) and ethanol sec-butanolamine (A1) are such that the molar ratio of ethanol di-sec-butanolamine (A2) to ethanol sec-butanolamine (A1) in the obtained composition (AC) is as defined above, for example (0.2-6):1, preferably (0.25-5.5):1, preferably (0.3-5):1, preferably (0.4-4.5):1, preferably (0.5-4):1, (0.6-3.8):1, preferably (0.7-3.5):1, preferably (0.8-3.3):1, preferably (0.9-3.2):1, preferably (1-3):1, preferably (1.2-2.8):1, thereby obtaining an alcoholamine composition (AC);

[0041] Wherein, the total amount of water used in step 1) and step 2) should be such that the water content in the (final) obtained alcoholamine composition (AC) is 9-30wt%, preferably 10-29wt%, preferably 11-28wt%, preferably 12-27wt%, preferably 13-26wt%, preferably 14-25wt%, preferably 15-24wt%, preferably 16-23wt%, preferably 17-22wt%, based on the total weight of the (final) alcoholamine composition (AC);

[0042] Preferably, in the (final) obtained alkanolamine composition (AC), the total content of (A1) + (A2) + water is as defined above, i.e. 92-100 wt %, preferably 93-100 %, preferably 94-100 %, preferably 95-100 %, preferably 96-100 %, preferably 97-100 %, preferably 98-100 %, preferably 99-100 %, such as 99.5 %, 99.8 %, 99.9 %, based on the total weight of the (final) alkanolamine composition (AC);

[0043] 4) introducing CO2 gas into the obtained alcoholamine composition (AC) to partially neutralize the alcoholamine compound in the composition (AC), thereby obtaining a (final) alcoholamine composition (AC) containing CO2 and water;

[0044] Among them, the amount of CO2 introduced should be such that the CO2 content in the (final) alkanolamine composition (AC) is 1-6wt%, preferably 1.2-5.5wt%, preferably 1.5-5.0wt%, preferably 1.8-4.7wt%, preferably 2-4.5wt%, preferably 2.5-4.0wt%, such as 3 or 3.5wt%, based on the total weight of the (final) alkanolamine composition (AC).

[0045] Preferably, for the above-mentioned olamine composition (AC), the CO2 content in the olamine composition (AC) is not higher than 7 wt% (more preferably not higher than 6.5 wt%, more preferably not higher than 6 wt%). If the CO2 content in the olamine composition (AC) is higher than 7 wt%, this may cause the sprayed, cured polyurethane foam layer to often crack from the substrate (e.g., concrete or stainless steel pipe or stainless steel plate) to form cracks or to crack between two adjacent foam layers to form cracks (delamination).

[0046] The inventors of the present application unexpectedly found that the aqueous alcoholamine composition (AC) of the present invention is a low-viscosity liquid at room temperature, which may be because ethanol sec-butanolamine and ethanol di-sec-butanolamine have an asymmetric structure, are not easy to associate and crystallize, and are mixed with each other, resulting in the low viscosity of the alcoholamine composition (AC). Generally, the viscosity or dynamic viscosity (25°C) of the aqueous alcoholamine composition (AC) is 200-1000 centipoise (mPa.s), preferably 220-900, more preferably 240-800, more preferably 250-700 centipoise, for example 280, 300, 400, 500, 650, 750 or 850 centipoise. For example, as a single compound, the freezing points (melting points) of diisopropanolamine and triisopropanolamine are 42° C. and 45° C., respectively, and at room temperature, diisopropanolamine and triisopropanolamine are white crystals or solid powders, which indicates that symmetrical diisopropanolamine and triisopropanolamine have a strong tendency to crystallize or associate. Therefore, in order to ensure that the alcoholamine composition (AC) of the present invention has a lower viscosity, it is desirable not to add diisopropanolamine and triisopropanolamine to the alcoholamine composition (AC) as much as possible.

[0047] Typically, the pH value of the alcoholamine composition (AC) containing alcoholamine partially neutralized by CO2 is in the range of 8-13.5, preferably 8-12, preferably 8.5-11.5, more preferably 9-11, preferably 9.1-10.5, preferably 9.2-10.

[0048] Actually, the aqueous alcoholamine composition (AC) of the present invention comprises alcoholamine carbonate+water+free alcoholamine, and therefore, it is a composite foaming agent with low viscosity.

[0049] In the present application, "optional" means with or without (0).

[0050] In addition, the inventors of the present application unexpectedly discovered that the above-mentioned aqueous alcohol amine composition (AC) (IV) of the present invention has good miscibility (or compatibility) in the dry white material formed by (I) polymer polyol and (II) and (III), and after being mixed, they can form a transparent, homogeneous and low-viscosity white material (i.e., a foaming polymer polyol composition for preparing polyurethane rigid foam).

[0051] The above-mentioned alcohol amine composition (AC) of the present invention is directly used as a foaming agent for preparing polyurethane rigid foam, and is particularly suitable for use in the spraying of polyurethane foam.

[0052] The present invention also relates to the use of the above-mentioned alcoholamine composition (AC) as a blowing agent for preparing (spray-type) rigid polyurethane foam materials, especially as a blowing agent for spraying rigid polyurethane foam.

[0053] The thermal conductivity λ (w / m·k, 20°C) of the spray polyurethane rigid foam of the present invention is generally lower than 0.02240, preferably lower than 0.02230, more preferably lower than 0.02225, more preferably lower than 0.02220, more preferably lower than 0.02210, more preferably lower than 0.02205.

[0054] The compressive strength of the spray polyurethane rigid foam of the present invention (in the direction perpendicular to the substrate, for example, when the density of the foam is about 38.5-40 Kg / cm 3 ) is 330-345 (KPa), preferably 337-345 (KPa).

[0055] Advantages of the present invention

[0056] 1. The present invention combines low-activity polymer polyols with high-activity polyether polyols, and at the same time, only a part of the olamine in the olamine composition (AC) is neutralized by CO2, which can successfully avoid the following problems often encountered in the prior art: when the mixture of white material and black material is sprayed onto a substrate (stainless steel or concrete) or onto a cured foam layer, the wet foam expands rapidly and falls off the substrate or the cured foam layer, and in addition, the cured foam has high brittleness, so it shrinks and deforms slightly, resulting in cracks between the cured foam material and the substrate or between two adjacent cured foam layers. These problems are particularly prominent when spraying in cold winter.

[0057] 2. Pentaerythritol-started polyether polyols and sorbitol-started polyether polyols have good compatibility with "ethanol sec-butanolamine and ethanol di-sec-butanolamine" in the chemical foaming agent (AC), have appropriate hydroxyl values, and are conducive to the formation of fine bubbles. Polycarbonate polyols and polytetrahydrofuran ether diols have low activity, thereby reducing the overall reactivity of the white material, and are also conducive to improving the toughness of the produced foam and reducing brittleness. Glycerol-started polyether polyols play the role of diluent (reducing the viscosity of the white material) and cross-linking agent (improving the strength and hardness of the foam).

[0058] 3. Compared with the salts of alcohol amines with two or three carbon atoms (diethanolamine carbonate and diisopropanolamine carbonate), ethanol sec-butanolamine and ethanol di-sec-butanolamine have lower reactivity and PU catalysis, making the foaming process smoother. Part of ethanol sec-butanolamine and ethanol di-sec-butanolamine form carbonates with CO2 and water, that is, the alcohol amines are partially salified. This alcohol amine composition (AC) is used as a blowing agent alone with a blowing agent for preparing dimensionally stable, low-brittle polyurethane rigid foams in polyurethane foam spraying.

[0059] 4. On the one hand, due to the structural asymmetry of the olamine molecules and the mutual doping between different olamines, the olamine composition (AC) of the present invention has a lower viscosity, so that the prepared white material has good fluidity, and therefore, it is suitable as a blowing agent for the spraying of polyurethane rigid foam. On the other hand, they have good compatibility or miscibility with the dry white material for foaming, so they can be easily and quickly mixed with the dry white material for foaming (to achieve miscibility at the molecular level) to form a uniform, transparent (homogeneous) and well-fluid foaming system (white material), and in the foaming reaction they have a nucleation effect (foaming point) to promote uniform foaming, and therefore, a spray polyurethane rigid foam with a fine pore microstructure (a large number of pores per unit volume, and uniform pore size), closed cell rate and strength properties can be obtained.

[0060] 5. In the early stage of the foaming process using the foaming agent composition, the carbonate alcohol amine salt hydrate produces a good nucleation effect, that is, the embryonic form of the foam cells. The early nucleation effect and the uniform foaming caused by the good compatibility and mixing of the foaming agent and the polymer polyol make the final PU foam have a fine microscopic cell structure: the size of the cells is smaller, the size of the cells is more uniform, the number of cells per unit volume is more (from the SEM photo, the number of cells per unit area is more), the alcohol amine and water make the cell wall more fully cross-linked (the foam has a higher strength at a lower foam density), the cell wall is thinner, the cell has a higher air tightness (attributed to the fully cross-linked network on the cell wall), and the closed cell rate is higher. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 is a SEM photograph of the foam of Example 1.

[0062] Figure 2 This is a SEM photograph of the foam of Example 2.

[0063] Figure 3 This is a SEM photograph of the foam of Example 3.

[0064] Figure 4 is a SEM photograph of the foam of Comparative Example 1.

[0065] Figure 5 is a SEM photograph of the foam of Comparative Example 2.

[0066] Figure 6 is a photograph of a cross section of the foam of Comparative Example 2.

[0067] Figure 7 The product of Preparation Example 6 (reference) 1 H-NMR spectrum.

[0068] Figure 8 The product of Preparation Example 7 (reference) 1 H-NMR spectrum.

[0069] Reference numerals: 2: crack between two adjacent foam layers; 3: substrate (cement board). DETAILED DESCRIPTION

[0070] The present invention further describes the technical scheme in detail through the following examples, but the present invention is not limited to these examples.

[0071] Unless otherwise specified, the devices used in the examples are all devices commonly used in the art and commercially available on the market.

[0072] Method for measuring the content of alcoholamines: In the embodiments, the method for measuring the content of various alcoholamines (e.g., ethanol isopropanol, ethanol sec-butanolamine, ethanol diisopropanolamine, ethanol di-sec-butanolamine or tri-sec-butanolamine) in the aqueous alcoholamine mixture (AC) (or aqueous alcoholamine composition or alcoholamine hydrate) can be performed by gas chromatography, wherein the gas chromatograph is equipped with a hydrogen flame ionization detector (FID), and the mass concentration of the alcoholamine compound is about 10 mg / mL, which is a standard solution. Gas chromatography conditions: HP-5 capillary column (30m×0.32mm id×0.25μm, 5% phenyl methyl-siloxane); the column temperature was programmed, the initial temperature was 80℃, maintained for 3min, then increased to 250℃ at a rate of 25℃ / min, and maintained for 5min; the injection port temperature was 250℃; the detector temperature was 260℃; the carrier gas was high-purity nitrogen with a flow rate of 1.5mL / min; the fuel gas was hydrogen with a flow rate of 30mL / min; the auxiliary gas was air with a flow rate of 300mL / min; the tail gas was nitrogen with a flow rate of 25mL / min; the injection method was split injection, with a split ratio of 30:1; the injection volume was 1μL.

[0073] In the present application, as pentaerythritol starting polyether polyols with a hydroxyl value between 430-580 mgKOH / g, polyether polyols H4039 (hydroxyl value 560-580 mgKOH / g) and H8404 (hydroxyl value 435-465 mgKOH / g) of Hongbaoli Group Co., Ltd. can be used.

[0074] As the polycarbonate polyol having a hydroxyl value of 100-280 mgKOH / g, SYHP1000 polycarbonate polyol produced by Shanghai Shuyu Chemical Co., Ltd. and bisphenol A type polycarbonate polyol produced by Hubei Chengfeng Chemical Co., Ltd. can be used.

[0075] As the sorbitol-started polyether polyol with a hydroxyl value between 340 and 520 mgKOH / g, polyether polyol 8038 (sorbitol initiator, hydroxyl value 380 mg KOH / g) of Jiahua Chemical Co., Ltd., polyether polyol H5021 (hydroxyl value 355-385 mgKOH / g) and H635SG (hydroxyl value 485-515 mgKOH / g) of Hongbaoli Group Co., Ltd., and polyether polyol YD-635 (hydroxyl value 490±15 mgKOH / g) and YD-6205 (hydroxyl value 380±15 mgKOH / g) of Hebei Yadong Chemical Group Co., Ltd. can be used.

[0076] As the polytetramethylene ether diol, polytetramethylene ether diol having a number average molecular weight of 800-2500, preferably 1000-2000, such as PTMG1000 and PTMG2000 of Jinan Yuyi Chemical Co., Ltd. can be used.

[0077] As glycerol-started polyether polyols with a hydroxyl value between 220-440 mgKOH / g, polyether polyols H304 (hydroxyl value 405-435 mgKOH / g), H305 (hydroxyl value 320-350 mgKOH / g) and H307 (hydroxyl value 225-255 mgKOH / g) of Hongbaoli Group Co., Ltd. can be used.

[0078] Commonly used catalysts are selected from: 33LV (A-33): 33% triethylenediamine in dipropylene glycol solution, N,N-dimethylethanolamine, N,N-dimethylbenzylamine, 70% bis(dimethylaminoethyl) ether in dipropylene glycol solution, 70% potassium octoate in diethylene glycol solution, dibutyltin dilaurate, PT303, PT304, potassium acetate, PC-8 (N,N-dimethylcyclohexylamine), PC-5 (N,N,N,N,N-pentamethyldiethylenetriamine), PC-41 (tris(dimethylaminopropyl)hexahydrotriazine), triethanolamine, JXP-508, JXP-509, TMR-2 (2-hydroxy-N,N,N-trimethyl-1-propylamine formate, Air Products and Chemicals, USA), TMR-3, TMR-4, Dabco 2040 (Evonik Chemicals). Commonly used silicone oil foam stabilizers or silane surfactants: B8525 and B8408 of Evonik Degussa (China) Investment Co., Ltd., AK-158, AK-8805, AK-8812, AK-8809, AK-8818 and AK-8860 of Jiangsu Meside Chemical Co., Ltd., DC8545, DC1990, DC5188, DC6070, DC3042 and DC3201 of Gas & Chemicals, and silicone oil 8841 of Shanghai Maihao Chemical Technology Co., Ltd. Non-silane surfactants: LK-221 and LK-443 of Gas & Chemicals. Commonly used flame retardants: flame retardant TCPP (Jiangsu Yak Chemical Co., Ltd.), TCPP (Qingdao Lianmei Chemical Co., Ltd.), TCEP, DMMP, ammonium chloride, aluminum hydroxide powder, DM1201, DM1301, tetrabromophthalic anhydride diol.

[0079] The following describes a method for preparing an amine carbonate chemical foaming agent (i.e., an amine carbonate hydrate) by CO2 aeration.

[0080] The water content of the carbonate ethanolamine salt hydrate measured by the Karl Fischer method = the amount of free water in the hydrate + the amount of water produced by the decomposition of the carbonate and optionally the bicarbonate. Therefore, the content of free water (wt%) in the carbonate ethanolamine salt chemical blowing agent (F1) (i.e., carbonate ethanolamine salt hydrate) = (the water content of the carbonate ethanolamine salt hydrate measured by the Karl Fischer method) - (the amount of water produced by the decomposition of the carbonate and optionally the bicarbonate). For example, the water content in the alcoholamine composition (AC) described in the present application refers to the water content measured by the Karl Fischer method.

[0081] The test methods for various parameters of polyurethane rigid foam are carried out with reference to the following Chinese national standards GB:

[0082]

[0083] In the above table, the Z direction represents the vertical direction of the foam sample (i.e., the direction perpendicular to the substrate), and the X direction and the Y direction represent two mutually perpendicular directions on the same horizontal plane of the sample.

[0084] Viscosity refers to the dynamic viscosity "centipoise (cP)" at 25°C.

[0085] Preparation Example 1

[0086] 24.42 kg of ethanolamine (molecular weight 61, 400.3 mol) and 13.56 kg of deionized water were added to the autoclave, stirred and dissolved, and the reactor was sealed. Then, under continuous stirring, the temperature was controlled between 60-95° C., and the pressure in the reactor was controlled not to be higher than 0.3 MPa. 51.96 kg of 1,2-butylene oxide (molecular weight 72.11, 720.5 mol, the molar ratio of 1,2-butylene oxide to ethanolamine was 1.8:1) was added to the reactor in batches. After the addition of the materials, the temperature was controlled to react for 3 hours, and then the temperature was lowered to 40° C. Then, 89.72 kg of the reaction product (alcoholamine hydrate AA1a, or alcoholamine composition AA1a) was discharged from the reactor, and the viscosity (25° C.) was 382 centipoise. The product was sampled and the content of ethanol sec-butanolamine in the amine hydrate AA1a was measured by gas chromatography to be 80.9 mol, the content of ethanol di-sec-butanolamine was 323.1 mol, and the molar ratio of ethanol di-sec-butanolamine to ethanol sec-butanolamine was 4: 1. The water content in the amine hydrate AA1a was measured by Karl Fischer method to be 15.0 wt%.

[0087] Then, 40 kg of the above obtained alcoholamine hydrate AA1a was added to an autoclave, and carbon dioxide gas was introduced into the alcoholamine hydrate AA1a under the condition that the pressure of the CO2 gas output from the CO2 storage cylinder was controlled to be no higher than 0.3 MPa, and the temperature was controlled between 40-50°C, and the temperature was controlled to react for 3 hours. After the temperature was lowered to below 40°C, the pressure was released and the product was discharged to obtain a carbonate alcoholamine salt composition AA1b (or alcoholamine composition AA1b), wherein the CO2 absorption amount was 748 g (about 17 mol, i.e., 19.05 mol% of the alcoholamine in AA1a was neutralized by CO2 to form carbonate alcoholamine salt; CO2 content was 1.83 wt%). The dynamic viscosity (25°C) of the product AA1b was 515 centipoise. The pH of the product AA1b was measured by a pH meter (Ray Magnet PHS-3C, Shanghai Yidian Science Instrument Co., Ltd.) and was 10.6. Its decomposition temperature is between 45℃ and 65℃.

[0088] Preparation Example 2

[0089] 24.42 kg of ethanolamine (molecular weight 61, 400.3 mol) and 15.0 kg of deionized water were added to a high-pressure reactor, stirred to dissolve, and the reactor was sealed. Then, under continuous stirring, the temperature was controlled between 60-95° C., and the pressure in the reactor was controlled not to be higher than 0.3 MPa. 43.45 kg of 1,2-butylene oxide (molecular weight 72.11, 602 mol, the molar ratio of 1,2-butylene oxide to ethanolamine was 1.5:1) was added to the reactor in batches. After the addition of the materials, the temperature was controlled to react for 3 hours, and then the temperature was lowered to 40° C. Then, 82.68 kg of the reaction product (alkanolamine hydrate AA2a, or alkanolamine composition AA2a) was discharged from the reactor, and samples were taken from the product and measured by gas chromatography to find that the content of ethanol sec-butanolamine in the alkanolamine hydrate AA2a was 200.03 mol, the content of ethanol di-sec-butanolamine was 199.95 mol, and the molar ratio of ethanol di-sec-butanolamine to ethanol sec-butanolamine was 1: 1. The water content in the alkanolamine hydrate AA2a was 18.0 wt%.

[0090] Then, 40kg of the above obtained alcoholamine hydrate AA2a is added to the autoclave, and the CO output from the CO storage cylinder is controlled under the condition that the pressure of the gas is not higher than 0.3MPa, and carbon dioxide gas is introduced into the alcoholamine hydrate AA2a, and the temperature is controlled between 40-50°C, and the temperature control reaction is performed for 3 hours. After the temperature is lowered to below 40°C, the pressure is released and the product is discharged to obtain a carbonate alcoholamine salt composition AA2b, wherein the CO absorption capacity is 1.50kg (about 34mol, CO content is 3.61wt%, and about 35.1mol% of the alcoholamine in AA2a is neutralized by CO to form carbonate alcoholamine salt. The viscosity (25°C) of the product AA2b is 693 centipoises. pH=10.2, and the decomposition temperature is between 45°C and 65°C.

[0091] Preparation Example 3

[0092] 30 kg of ethanolamine (molecular weight 61, 491.8 mol) and 14 kg of deionized water were added to the autoclave, stirred and dissolved, and the reactor was sealed. Then, under continuous stirring, the temperature was controlled between 60-95° C., and the pressure in the reactor was controlled to be no higher than 0.3 MPa. 42.6 kg of 1,2-butylene oxide (590 mol, the molar ratio of 1,2-butylene oxide to ethanolamine was 1.2:1) was added to the reactor in batches. After the addition of the materials, the temperature was controlled to react for 3 hours, and then the temperature was lowered to 40° C. Then, 86.4 kg of the reaction product (alcoholamine hydrate AA3a) was discharged from the reactor. Samples were taken from the product and the content of ethanol sec-butanolamine in the alcoholamine hydrate AA3a was measured by gas chromatography to be 393.2 mol, 98.3 mol of ethanol di-sec-butanolamine, and the molar ratio of ethanol di-sec-butanolamine to ethanol sec-butanolamine was 0.25:1. The water content in the alcoholamine hydrate AA3a was 16.0 wt %.

[0093] Then, 40 kg of the above obtained alcoholamine hydrate AA3a is added to an autoclave, and carbon dioxide gas is introduced into the alcoholamine hydrate AA3a under the condition that the pressure of the CO2 gas output from the CO2 storage cylinder is not higher than 0.3 MPa, and the temperature is controlled between 40-50° C., and the temperature is controlled to react for 3 hours. After the temperature is lowered to below 40° C., the pressure is released and the product is discharged to obtain a carbonate alcoholamine salt composition AA3b, wherein the CO2 absorption capacity is 1.85 kg (about 42 mol, CO2 content is 4.42 wt%, and 36.9 mol% of the alcoholamine in AA3a is neutralized by CO2). The viscosity (25° C.) of the product AA3b is 757 centipoises. pH=11.0.

[0094] Preparation Example 4

[0095] Part I: Preparation of single alcohol amines

[0096] 1) 30.5 kg of ethanolamine (molecular weight 61, 500 mol) and 15.5 kg of deionized water were added to a high-pressure reactor, stirred and dissolved, and the reactor was sealed. Then, under continuous stirring, the temperature was controlled between 60-95°C and the pressure was controlled not to be higher than 0.25 MPa. 36.07 kg of 1,2-butylene oxide (molecular weight 72.11, 500 mol) was added to the reactor in batches. After the addition of the materials, the temperature was controlled to react for 3.5 hours, and then the temperature was lowered to 40°C. Then, 82.01 kg of the reaction product (alcoholamine hydrate AA4a) was discharged from the reactor. Samples were taken from the product and the content of ethanol sec-butanolamine in the alcoholamine hydrate AA4a was measured by gas chromatography to be 499.94 mol and 0.06 mol of ethanol di-sec-butanolamine. Its viscosity (25°C) was 372 centipoise. The water content in the alcoholamine hydrate AA4a was 18.89 wt%. The pH value was 12.21.

[0097] 2) 30.5 kg of ethanolamine (molecular weight 61,500 mol) and 22.55 kg of deionized water were added to the autoclave, stirred and dissolved, and the reactor was sealed. Then, under continuous stirring, the temperature was controlled between 60-95°C and the pressure was controlled not to be higher than 0.25 MPa. 72.12 kg of 1,2-butylene oxide (1000 mol) was added to the reactor in batches. After the addition of the materials, the temperature was controlled to react for 3.5 hours, and then the temperature was lowered to 40°C. Then, 125.02 kg of the reaction product (alcoholamine hydrate AA4b) was discharged from the reactor. Samples were taken from the product and the content of ethanol di-sec-butanolamine in the alcoholamine hydrate AA4b was 499.97 mol and the content of ethanol sec-butanolamine was 0.03 mol by gas chromatography. Its viscosity (25°C) was 464 centipoise. The water content in the alcoholamine hydrate AA4b was 18.0 wt%. The pH value was 11.56.

[0098] Part II: Compounding of Multiple Alkylamines (Formulation Design)

[0099] 1) The product AA4b and the product AA4a are mixed in a molar ratio of 4:1 of ethanol di-sec-butanolamine to ethanol sec-butanolamine; CO2 gas is then introduced, and the CO2 content in the alcohol amine composition is 1.02 wt%, based on the weight of the alcohol amine composition product. The alcohol amine composition AA4-1 is obtained, and its viscosity (25° C.) is 523 centipoise.

[0100] 2) AA4b and AA4a were mixed in a molar ratio of 1:1 of ethanol di-sec-butanolamine to ethanol sec-butanolamine; CO2 gas was then introduced, and the CO2 content in the ethanolamine composition was 3.57 wt %, to obtain an ethanolamine composition AA4-2, whose viscosity (25° C.) was 658 centipoise.

[0101] 3) AA4b and AA4a were mixed in a molar ratio of 0.25:1 of ethanol di-sec-butanolamine to ethanol sec-butanolamine; CO2 gas was then introduced, and the CO2 content in the ethanol amine composition was 3.83 wt %, to obtain an ethanol amine composition AA4-3, whose viscosity (25° C.) was 608 centipoise.

[0102] Preparation Example 5 (Comparative)

[0103] A carbonate amine salt composition product with a higher CO2 content was obtained as a comparison.

[0104] 30 kg of the alcoholamine hydrate AA3a obtained by the method of the above preparation example 3 was added to the autoclave, and carbon dioxide gas was introduced into the alcoholamine hydrate AA3a under the condition that the pressure of the CO2 gas output from the CO2 storage cylinder was controlled to be 0.3 MPa, and the temperature was controlled between 40-50° C. The temperature was controlled to react for 3 hours, and the pressure was released after the temperature was lowered to below 40° C., and the product was discharged to obtain an alcoholamine carbonate compound AA5b (or alcoholamine composition), wherein the CO2 absorption amount was 2.42 kg (about 55 mol, CO2 content was 7.46 wt%, and about 64.4 mol% of the alcoholamine was neutralized by CO2). The viscosity (25° C.) of the product AA5b was 1542 centipoise. pH=10.4.

[0105] Preparation Example 6 (reference)

[0106] 24.42 kg of ethanolamine (molecular weight 61, 400.3 mol) and 12.24 kg of deionized water were added to a high-pressure reactor, stirred to dissolve, and the reactor was sealed. Then, under continuous stirring, the temperature was controlled between 60-95° C., and the pressure in the reactor was controlled to be no higher than 0.3 MPa. 41.8 kg of propylene oxide (molecular weight 58, 720 mol, the molar ratio of propylene oxide to ethanolamine was 1.8:1) was added to the reactor in batches. After the addition of the materials, the temperature was controlled to react for 3 hours, and then the temperature was lowered to 40° C. Then, 78.31 kg of the reaction product (alcoholamine hydrate AA6a, or alcoholamine composition AA6a) was discharged from the reactor, and the viscosity (25° C.) was 291 centipoise. The product was sampled and the content of ethanol isopropanolamine in the amine hydrate AA6a was measured by gas chromatography. The content of ethanol diisopropanolamine was 80.1 mol, the content of ethanol diisopropanolamine was 319.8 mol, and the molar ratio of ethanol diisopropanolamine to ethanol isopropanolamine was 4:1. 1 H-NMR spectrum is shown in Figure 7 The water content of the alcoholamine hydrate AA6a was determined by Karl Fischer method to be 15.6 wt %.

[0107] Then, 40 kg of the above obtained alcohol amine hydrate AA6a is added to the autoclave, and carbon dioxide gas is introduced into the alcohol amine hydrate AA6a under the condition that the pressure of the CO2 gas output from the CO2 storage cylinder is not higher than 0.3 MPa, and the temperature is controlled between 40-50 ° C, and the temperature control reaction is performed for 3 hours. After the temperature is lowered to below 40 ° C, the pressure is released and the product is discharged to obtain a carbonate alcohol amine salt composition AA6b (or referred to as alcohol amine composition AA6b), wherein the CO2 absorption is 792 g (about 18 mol, i.e., 17.5 mol% of the alcohol amine in AA6a is neutralized by CO2 to form carbonate alcohol amine salt; CO2 content is 1.94 wt%). The dynamic viscosity (25 ° C) of the product AA6b is 489 centipoise. The pH of the product AA6b measured by a pH meter (Ray Magnetic PHS-3C type, Shanghai Yidian Science Instrument Co., Ltd.) is 10.8. Its decomposition temperature is between 45℃ and 68℃.

[0108] Preparation Example 7 (reference)

[0109] 17.64 kg of 1,4-diamine (molecular weight 88.15, 200 mol) and 9.2 kg of deionized water were added to a high-pressure reactor, stirred and dissolved, and the reactor was sealed. Then, under continuous stirring, the temperature was controlled between 60-95°C and the pressure was controlled not to be higher than 0.3 MPa. 23.232 kg of propylene oxide (molecular weight 58.079, 400 mol) was added to the reactor in batches. After the addition, the temperature was controlled to react for 3 hours, and then the temperature was lowered to 40°C. Then, about 50 kg of the reaction product (alcoholamine hydrate AA7a) was discharged from the reactor, and the pH value of the product measured by a pH meter was 13.46. Samples were taken from the product and the content of N,N,N'-tri(hydroxyisopropyl)-diamine in the alcoholamine hydrate AA7a was measured by gas chromatography to be about 0.02 mol, and the content of N,N'-di(hydroxyisopropyl)-diamine was about 199.98 mol. Its viscosity (25°C) is 324 centipoise. The water content of the alcoholamine hydrate AA7a measured by Karl Fischer method is 18.4 wt%. A sample is taken from the obtained product for testing NMR spectrum. 1 H-NMR shows Figure 8 . Figure 8 It shows that the product of Preparation Example 7 is N,N'-di(hydroxyisopropyl)-butylene diamine. This shows that the alcohol amine product obtained by the reaction of organic amine and epoxide depends on the molar ratio of organic amine to epoxide. This alcohol amine product can also be used as a component of PU foaming agent.

[0110] Application Examples

[0111] Example 1

[0112] 1. Raw materials of white component: weigh 55kg polyether polyol H4039 (hydroxyl value 560-580mgKOH / g, pentaerythritol starting polyether polyol, Hongbaoli Group Co., Ltd.), 18kg polycarbonate polyol SYHP1000 (hydroxyl value 230-250mgKOH / g, Shanghai Shuyu Chemical Co., Ltd.), 12kg polyether polyol 8038 (sorbitol starting agent, hydroxyl value 380mg KOH / g, Jiahua Chemical Co., Ltd.), 9kg polytetramethylene glycol PTMG1000 (number average molecular weight 1000, Jinan Yuyi Chemical Co., Ltd.), 6kg glycerol-started polyether polyol H304 (hydroxyl value 405-435mgKOH / g, Hongbaoli Group Co., Ltd.), 1kg catalyst TMR-2 (Air Chemicals, USA), 0.1kg catalyst Dabco2040 (Evonik Chemical), 2kg foam stabilizer DC3201 (Gas and Chemicals Company), 15kg flame retardant TCPP (Jiangsu Yak Chemical Co., Ltd.), 11kg of the carbonate amine salt composition AA1b in Preparation Example 1 (wherein the molar ratio of ethanol di-sec-butanolamine (A2) to ethanol di-sec-butanolamine (A1) is 4:1, and the CO2 content is 1.83wt%).

[0113] 2. Add the weighed polyether polyol H4039, polycarbonate polyol SYHP1000, polyether polyol 8038, polytetramethylene glycol PTMG1000, glycerol-started polyether polyol H304, catalysts TMR-2 and Dabco2040, foam stabilizer DC3201, flame retardant TCPP, and carbonate amine salt composition AA1b into the reactor in sequence, and stir slowly (180 rpm) for 2 hours at room temperature to mix them completely to obtain a uniform, transparent mixture (i.e., the white material component).

[0114] 3. The black material component is polymethyl polyphenyl polyisocyanate (PM200, Wanhua Chemical), with a dosage of 130 kg.

[0115] 4. At an ambient temperature of 25°C, the white component and the black component were sprayed onto a vertical cement board (substrate) at a temperature of 25°C by a Graco sprayer A-25. The foam was sprayed and foamed in a spraying manner with each layer of foam being 2-3cm thick and the total thickness of the foam being 20cm. During the spraying process, no phenomenon of wet foam falling off in the form of larger pieces or blocks was observed. After the foam was formed and matured, a polyurethane rigid foam material was obtained. The performance parameters of the obtained foam product are listed in Table 1.

[0116] The cured polyurethane foam on the cement board (substrate) was cut open with an electric saw and the cross section was observed. No peeling of the cured foam from the substrate was found.

[0117] The SEM images of the foam samples are shown in Figure 1 The cell size of the foam is very uniform.

[0118] Example 2

[0119] Example 1 was repeated, except that the same amount of the alcohol amine composition AA2b of Preparation Example 2 (wherein the molar ratio of ethanol di-sec-butanolamine (A2) to ethanol di-sec-butanolamine (A1) was 1:1, and the CO2 content was 3.61 wt%) was used instead of the carbonate alcohol amine salt composition AA1b to prepare a polyurethane rigid foam material. The cell size was very uniform. In the spraying process, no phenomenon of wet foam falling off in the form of larger pieces or blocks was observed, and no phenomenon of foam peeling off from the substrate was found after curing. The SEM photograph of the foam material sample is shown in Figure 2 .

[0120] Example 3

[0121] Example 1 was repeated, except that the same amount of the alcoholamine composition AA3b (the molar ratio of A2 to A1 was 0.25:1, and the CO2 content was 4.42 wt%) of Preparation Example 3 was used instead of the carbonate alcoholamine salt composition AA1b to prepare a polyurethane rigid foam material. In the spraying process, no phenomenon of wet foam falling off in the form of large-sized flakes or blocks was observed, and no phenomenon of foam peeling off from the substrate was found after curing. The SEM photograph of the foam sample is shown in Figure 3 .

[0122] Comparative Example 1

[0123] The operation process is repeated in Example 1, except that the amount of polyether polyol 8038 (sorbitol initiator, hydroxyl value 380mg KOH / g, Jiahua Chemical Co., Ltd.) is changed from 12kg to 17kg, the amount of glycerol-started polyether polyol H304 (hydroxyl value 405-435mgKOH / g, Hongbaoli Group Co., Ltd.) is changed from 6kg to 10kg, and polytetramethylene glycol PTMG1000 is not used.

[0124] The performance parameters of the foam products are listed in Table 1. The SEM images of the foam samples are shown in Figure 4 .

[0125] Comparative Example 2

[0126] The operation was repeated as in Example 1, except that the carbonate amine salt composition AA5b having a higher CO2 content of Preparation Example 5 (Comparative) was used instead of the carbonate amine salt composition AA1b.

[0127] 1. Raw materials of white component: weigh 55kg polyether polyol H4039 (hydroxyl value 560-580mgKOH / g, pentaerythritol starting polyether polyol, Hongbaoli Group Co., Ltd.), 18kg polycarbonate polyol SYHP1000 (hydroxyl value 230-250mgKOH / g, Shanghai Shuyu Chemical Co., Ltd.), 12kg polyether polyol 8038 (sorbitol starting agent, hydroxyl value 380mg KOH / g, Jiahua Chemical Co., Ltd.), 9kg polytetramethylene glycol PTMG1000 (number average molecular weight 1000, Jinan Yuyi Chemical Co., Ltd.), 6kg glycerol-started polyether polyol H304 (hydroxyl value 405-435mgKOH / g, Hongbaoli Group Co., Ltd.), 1kg catalyst TMR-2 (Air Chemicals, USA), 0.1kg catalyst Dabco2040 (Evonik Chemical), 2kg foam stabilizer DC3201 (Gas and Chemicals Company), 15kg flame retardant TCPP (Jiangsu Yak Chemical Co., Ltd.), 11kg of the carbonate amine salt composition AA5b in Preparation Example 5 (comparison) (wherein the molar ratio of ethanol di-sec-butanolamine (A2) to ethanol di-sec-butanolamine (A1) is 0.25:1, and the CO2 content is 7.46wt%).

[0128] 2. Add the weighed polyether polyol H4039, polycarbonate polyol SYHP1000, polyether polyol 8038, polytetramethylene glycol PTMG1000, glycerol-started polyether polyol H304, catalysts TMR-2 and Dabco2040, foam stabilizer DC3201, flame retardant TCPP, and carbonate amine salt composition AA5b into the reactor in sequence, and stir slowly (180 rpm) for 2 hours at room temperature to mix them completely to obtain a uniform, transparent mixture (i.e., the white material component).

[0129] 3. The black material component is polymethyl polyphenyl polyisocyanate (PM200, Wanhua Chemical), with a dosage of 130 kg.

[0130] 4. At an ambient temperature of 25°C, the white component and the black component were sprayed onto a vertical cement board (substrate) at a temperature of 25°C by a Graco sprayer A-25. The foam was sprayed in a spraying manner with each layer of foam being 2-3cm thick and the total foam thickness being 20cm. During the spraying process, it was observed that the wet foam fell in the form of larger blocks. After the foam was formed and matured, a polyurethane rigid foam material was obtained. The performance parameters of the obtained foam product are listed in Table 1. The SEM photo of the foam material sample is shown in Figure 5 .

[0131] The cured polyurethane foam on the cement board (substrate) was cut open with an electric saw, and the cross section was observed. It was found that cracks were formed between two adjacent foam layers (as shown by reference numeral 2). Figure 6 as shown in .

[0132] The results of Comparative Example 2 show that when a carbonate amine salt composition having a higher CO2 content is used, the wet foam is observed to fall off in the form of larger sized pieces during the spraying process, and for the cured foam, delamination is found to occur between adjacent foam layers.

[0133] Table 1 - Performance parameters of foam materials

[0134]

[0135] Note: The compressive strength is measured for the foam specimen in the Z direction (perpendicular to the substrate), and "cracking" means that the cured foam cracks from the substrate or cracks between two adjacent foam layers. "Slightly uniform" means that the cell size is moderately uniform.

[0136] The foam of Comparative Example 1 has lower compressive strength and dimensional stability (higher values) than the foam of Example 1, which indicates that the use of polytetramethylene glycol in the present invention can improve the toughness of the rigid PU foam.

[0137] As can be seen from Table 1 above, when the secondary butanolamine composition (AC) of the present invention is used as a chemical foaming agent in combination with a specific polymer polyol composition, there is no drop of wet foam during the spraying process, and the prepared polyurethane rigid foam material has excellent overall performance, stable size, low thermal conductivity and good thermal insulation performance.

Claims

1. A dimensionally stable polyurethane rigid foam, which is formed by mixing and spraying a polyisocyanate with a polymer polyol composition, wherein the polymer polyol composition comprises or consists of the following components: (I) 100 parts by weight of a polymer polyol, comprising: 1) 50-60 wt% of a pentaerythritol-based polyether polyol having a hydroxyl value in the range of 430-580 mgKOH / g; 2) 14-22 wt% of a polycarbonate polyol having a hydroxyl value in the range of 100-280 mgKOH / g; 3) 9-15 wt% of a sorbitol-based polyether polyol having a hydroxyl value in the range of 340-520 mgKOH / g; 4) 6-12 wt% of a polytetramethylene glycol having a number average molecular weight in the range of 800-2500; 5) 4-8 wt% of a glycerol-based polyether polyol having a hydroxyl value in the range of 220-440 mgKOH / g; wherein the weight percentages are based on the total amount of components 1) to 5); (II) 1.5-6.5 parts by weight of a catalyst and a foam stabilizer as auxiliary agents, wherein the auxiliary agents include 0.5-2.5 parts by weight of the catalyst and 1-4 parts by weight of the foam stabilizer relative to 100 parts by weight of the polymer polyol; (III) 0-18 parts by weight of a flame retardant relative to 100 parts by weight of the polymer polyol; (IV) 8-16 parts by weight of a CO2- and water-containing olamine composition (AC) as a blowing agent, relative to 100 parts by weight of the polymer polyol; the olamine composition (AC) comprises or consists of or is mainly composed of the following components: (1) ethanol sec-butanolamine (A1); (2) ethanol di-sec-butanolamine (A2); and (3) Water; Wherein, the molar ratio of ethanol di-sec-butanolamine (A2) to ethanol sec-butanolamine (A1) is (0.2-6):1; wherein the content of water is 9-30 wt %, based on the total weight of the alcoholamine composition (AC); wherein the total content of (A1) + (A2) + water is 92-100 wt %, based on the total weight of the (final) alcoholamine composition (AC); Wherein, a portion of the alkanolamine in the alkanolamine composition (AC) is neutralized by CO2 so that the content of CO2 in the alkanolamine composition (AC) is 1-6 wt% based on the total weight of the (final) alkanolamine composition (AC).

2. The polyurethane rigid foam according to claim 1, wherein Polymer polyols include: 1) 52-58wt% of pentaerythritol as starting polyether polyol, its hydroxyl value is in the range of 430-580mgKOH / g; 2) 16-20wt% of polycarbonate polyol, its hydroxyl value is in the range of 100-280mgKOH / g; 3) 10-14wt% of sorbitol as starting polyether polyol, its hydroxyl value is in the range of 340-520mgKOH / g; 4) 7-11wt% of polytetramethylene glycol, its number average molecular weight is in the range of 800-2500; 5) 5-7wt% of glycerol as starting polyether polyol, its hydroxyl value is in the range of 220-440mgKOH / g; wherein the weight percentages are based on the total amount of components 1)-5); and / or The amount of component (II) auxiliary agent is 2.5-5 parts by weight, including 1-2 parts by weight of catalyst and 1.5-3 parts by weight of foam stabilizer; and / or The flame retardant of component (III) is used in an amount of 4 to 16 parts by weight relative to 100 parts by weight of the polymer polyol; and / or The amount of component (IV) amine composition (AC) is 9-15 parts by weight; and / or In the alcoholamine composition (AC), the water content is 12-27 wt%; and / or A portion of the alcoholamine in the alcoholamine composition (AC) is neutralized by CO2 so that the content of CO2 in the alcoholamine composition (AC) is 1.5-5.0 wt%; and / or The total content of (A1)+(A2)+water is 93-100 wt %, based on the total weight of the alcoholamine composition (AC).

3. The polyurethane rigid foam according to claim 1 or 2, wherein 1) pentaerythritol-based polyether polyols having a hydroxyl value in the range of 440-570 mgKOH / g; 2) polycarbonate polyols having a hydroxyl value in the range of 110-270 mgKOH / g; 3) sorbitol-based polyether polyols having a hydroxyl value in the range of 350-500 mgKOH / g; 4) polytetrahydrofuran ether diols having a number average molecular weight in the range of 1000-2000; 5) glycerol-based polyether polyols having a hydroxyl value in the range of 240-420 mgKOH / g; and / or In the alcoholamine composition (AC), the water content is 14-25 wt%; and / or A portion of the alcoholamine in the alcoholamine composition (AC) is neutralized by CO2 so that the content of CO2 in the alcoholamine composition (AC) is 2-5.0 wt%; and / or The amount of component (IV) olamine composition (AC) is 10-14 parts by weight relative to 100 parts by weight of polymer polyol; and / or The molar ratio of ethanol di-sec-butanolamine (A2) to ethanol sec-butanolamine (A1) is (0.25-5.5):1; and / or The total content of (A1)+(A2)+water is 94-100 wt %, based on the total weight of the alkanolamine composition (AC).

4. The polyurethane rigid foam according to any one of claims 1 to 3, wherein In the alcoholamine composition (AC), the water content is 15-24 wt%; and / or A portion of the alcoholamine in the alcoholamine composition (AC) is neutralized by CO2 so that the content of CO2 in the alcoholamine composition (AC) is 3-5 wt%; and / or The molar ratio of ethanol di-sec-butanolamine (A2) to ethanol sec-butanolamine (A1) is (0.25-4):1; and / or The total content of (A1)+(A2)+water is 95-100 wt %, based on the total weight of the alcoholamine composition (AC).

5. The polysiloxane-polyurethane rigid foam according to claim 4, wherein: In the alcoholamine composition (AC), the water content is 16-23 wt%; and / or A portion of the alcoholamine in the alcoholamine composition (AC) is neutralized by CO2 so that the content of CO2 in the alcoholamine composition (AC) is 3.5-4.5 wt%; and / or The total content of (A1)+(A2)+water is 96-100 wt %, based on the total weight of the alcoholamine composition (AC).

6. The polyurethane rigid foam according to any one of claims 1 to 5, wherein 1) pentaerythritol-based polyether polyols having a hydroxyl value in the range of 450-560 mgKOH / g; 2) polycarbonate polyols having a hydroxyl value in the range of 120-260 mgKOH / g; 3) sorbitol-based polyether polyols having a hydroxyl value in the range of 360-490 mgKOH / g; 4) polytetrahydrofuran ether diols having a number average molecular weight in the range of 1000-2000; 5) glycerol-based polyether polyols having a hydroxyl value in the range of 250-400 mgKOH / g; and / or The amount of the component (IV) olamine composition (AC) is 10-12 parts by weight relative to 100 parts by weight of the polymer polyol.

7. The polyurethane rigid foam according to any one of claims 1 to 6, wherein When the density of the foam is 38.5-40Kg / cm 3 When the foam is subjected to pressure drop, the compressive strength of the foam is 330-345 (KPa), preferably 337-345 (KPa).

8. A method for preparing a polysiloxane-polyurethane rigid foam according to any one of claims 1 to 7, the method comprising mixing and spraying a polyisocyanate with a polymer polyol composition, wherein the polymer polyol composition comprises or consists of the following components: (I) 100 parts by weight of a polymer polyol, comprising: 1) 50-60 wt% of a pentaerythritol-based polyether polyol having a hydroxyl value in the range of 430-580 mgKOH / g; 2) 14-22 wt% of a polycarbonate polyol having a hydroxyl value in the range of 100-280 mgKOH / g; 3) 9-15 wt% of a sorbitol-based polyether polyol having a hydroxyl value in the range of 340-520 mgKOH / g; 4) 6-12 wt% of a polytetramethylene glycol having a number average molecular weight in the range of 800-2500; 5) 4-8 wt% of a glycerol-based polyether polyol having a hydroxyl value in the range of 220-440 mgKOH / g; wherein the weight percentages are based on the total amount of components 1) to 5); (II) 1.5-6.5 parts by weight of a catalyst and a foam stabilizer as auxiliary agents, wherein the auxiliary agents include 0.5-2.5 parts by weight of the catalyst and 1-4 parts by weight of the foam stabilizer relative to 100 parts by weight of the polymer polyol; (III) 0-18 parts by weight of a flame retardant relative to 100 parts by weight of the polymer polyol; (IV) 8-16 parts by weight of a CO2- and water-containing olamine composition (AC) as a blowing agent, relative to 100 parts by weight of the polymer polyol; the olamine composition (AC) comprises or consists of or is mainly composed of the following components: (1) ethanol sec-butanolamine (A1); (2) ethanol di-sec-butanolamine (A2); and (3) Water; Wherein, the molar ratio of ethanol di-sec-butanolamine (A2) to ethanol sec-butanolamine (A1) is (0.2-6):1; wherein the content of water is 9-30 wt %, based on the total weight of the alcoholamine composition (AC); wherein the total content of (A1) + (A2) + water is 92-100 wt %, based on the total weight of the (final) alcoholamine composition (AC); Wherein, a portion of the alkanolamine in the alkanolamine composition (AC) is neutralized by CO2 so that the content of CO2 in the alkanolamine composition (AC) is 1-6 wt% based on the total weight of the (final) alkanolamine composition (AC).

9. The method according to claim 8, wherein Polymer polyols include: 1) 52-58wt% of pentaerythritol as starting polyether polyol, its hydroxyl value is in the range of 430-580mgKOH / g; 2) 16-20wt% of polycarbonate polyol, its hydroxyl value is in the range of 100-280mgKOH / g; 3) 10-14wt% of sorbitol as starting polyether polyol, its hydroxyl value is in the range of 340-520mgKOH / g; 4) 7-11wt% of polytetramethylene glycol, its number average molecular weight is in the range of 800-2500; 5) 5-7wt% of glycerol as starting polyether polyol, its hydroxyl value is in the range of 220-440mgKOH / g; wherein the weight percentages are based on the total amount of components 1)-5); and / or The amount of component (II) auxiliary agent is 2.5-5 parts by weight, including 1-2 parts by weight of catalyst and 1.5-3 parts by weight of foam stabilizer; and / or The flame retardant of component (III) is used in an amount of 4 to 16 parts by weight relative to 100 parts by weight of the polymer polyol; and / or The amount of component (IV) amine composition (AC) is 9-15 parts by weight; and / or In the alcoholamine composition (AC), the water content is 12-27 wt%; and / or A portion of the alcoholamine in the alcoholamine composition (AC) is neutralized by CO2 so that the content of CO2 in the alcoholamine composition (AC) is 1.5-5.0 wt%; and / or The total content of (A1)+(A2)+water is 93-100 wt %, based on the total weight of the alcoholamine composition (AC).

10. The method according to claim 8 or 9, wherein 1) pentaerythritol-based polyether polyols having a hydroxyl value in the range of 440-570 mgKOH / g; 2) polycarbonate polyols having a hydroxyl value in the range of 110-270 mgKOH / g; 3) sorbitol-based polyether polyols having a hydroxyl value in the range of 350-500 mgKOH / g; 4) polytetrahydrofuran ether diols having a number average molecular weight in the range of 1000-2000; 5) glycerol-based polyether polyols having a hydroxyl value in the range of 240-420 mgKOH / g; and / or In the alcoholamine composition (AC), the water content is 14-25 wt%; and / or A portion of the alcoholamine in the alcoholamine composition (AC) is neutralized by CO2 so that the content of CO2 in the alcoholamine composition (AC) is 2-5.0 wt%; and / or The amount of component (IV) olamine composition (AC) is 10-14 parts by weight relative to 100 parts by weight of polymer polyol; and / or The molar ratio of ethanol di-sec-butanolamine (A2) to ethanol sec-butanolamine (A1) is (0.25-5.5):1; and / or The total content of (A1)+(A2)+water is 94-100 wt %, based on the total weight of the alkanolamine composition (AC).

Citation Information

Patent Citations

  • Process for separating components from ethanolamine mixtures

    CA1003358A

  • Novel preparation method for mono ethanol diisopropanolamine

    CN103435499A

  • Monoethanol diisopropanol amine production method

    CN107663157A

  • Process for the separation of monoethanolamine diethanolamine and triethanolamine from crude ethanolamine mixtures

    GB1387573A

  • A process for the production of mono-alkylolamines

    GB448373A